Cordless telecommunications worldwide the evolution of unlicensed PCS - Tuttlebee, Wally H. W. (Springer, 1997)
Cordless Telecommunications Worldwide describes the emergence of the global unlicensed PCS industry from initial developments in Europe to subsequent activities in Asia and America. This is related to the dynamic panorama of development, both in the available technology and in the market, which has occurred worldwide. Contributions from key industry players include: Evolution of the Cordless Telephone (unlicensed PCS) Market Applications; Standards Development Worldwide; New Digital Standard Products; Cordless Technology; Future Evolution of Cordless Telecommunications; Descriptions of Technical Standards including CT2, DECT, PHS, WCPE, and PACS. Comprehensive coverage of these issues will provide both managers and analysts in the telecommunications industry with valuable insights into and understanding of the market, the technologies and their interaction as well as likely future developments.